Extremely high HDL cholesterol paradoxically increases the risk of all-cause mortality in non-diabetic males from the Korean population: Korean genome and epidemiology study-health examinees (KoGES-HEXA) cohorts - Ryu, Ha-Eun; Jung, Dong Hyuk; Heo, Seok-Jae; Park, Byoungjin; Lee, Yong Jae (Frontiers in Medicine, 2025)
BackgroundHigh-density lipoprotein cholesterol (HDL-C) is associated with lower risk of mortality and cardiovascular disease. However, the relationship between extremely high HDL cholesterol level and all-cause mortality has not been thoroughly investigated. In this study, we examined the longitudinal effects of very high HDL cholesterol on all-cause mortality in a large cohort of Korean adults without type 2 diabetes mellitus.MethodsData from 173,195 Korean participants over 40 years of age enrolled in the Korean Genome and Epidemiology Study-Health Examinees (KoGES-HEXA) cohort, linked with the death certificate database of the National Statistical Office, were assessed. Participants were grouped into four according to HDL-C levels. We used multivariate Cox proportional-hazard regression models to prospectively assess hazard ratios (HRs) for all-cause mortality with 95% confidence intervals (CIs) over an 11-year baseline period.ResultsDuring a mean follow-up of 11.7 years, there were a total of 3,906 deaths from all causes, including 2,258 in men and 1,648 in women. The relationship between HDL-C and all-cause mortality showed a U-shaped pattern, especially in men. Compared to the reference group, the HR (95% CI) for mortality in males in the highest HDL cholesterol group was 1.31 (95% CI, 1.01–1.71) after adjusting for potential confounding variables. Moreover, low HDL cholesterol showed a statistically significant association with increased mortality in both men and women.ConclusionExtremely high HDL-C levels could paradoxically increase the risk of all-cause mortality, particularly among males, in the general population without type 2 diabetes mellitus. Non-protective effects of very high HDL-C level should be noted when predicting incident metabolic syndrome, particularly in men, in clinical settings.